1997
DOI: 10.1093/humrep/12.4.823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonographic findings in spontaneous abortions with normal and abnormal karyotypes

Abstract: To determine whether ultrasonographic findings can predict the karyotype of spontaneous abortions, 137 pregnancies (54 spontaneous, 83 assisted ovulatory cycles) that subsequently aborted and had chromosome analysis performed on the products of conception were studied ultrasonographically. Transvaginal ultrasound was performed using an Acuson 128XP/10 with 7.5 MHz probe. The numbers of empty gestational sacs, small and normal for gestational size, embryonic poles and embryos with documented cardiac activity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 11 publications
2
27
1
Order By: Relevance
“…Previous studies have shown different results for the correlation between a small embryonic pole and abnormal karyotypes [17,18] (Table 3). In this study, the abnormality rate in the small embryonic pole group was similar to that of the other groups, including the group with normal ultrasound findings, which is inconsistent with the results of Angiolucci et al [18].…”
Section: Ultrasound Findingsmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies have shown different results for the correlation between a small embryonic pole and abnormal karyotypes [17,18] (Table 3). In this study, the abnormality rate in the small embryonic pole group was similar to that of the other groups, including the group with normal ultrasound findings, which is inconsistent with the results of Angiolucci et al [18].…”
Section: Ultrasound Findingsmentioning
confidence: 85%
“…Goldstein et al and Coulam et al reported that ultrasound findings should not be used to predict the karyotypes associated with spontaneous miscarriages [16,17]. However, recent studies have demonstrated correlations between ultrasound findings and chromosomal anomalies [18,19].…”
Section: Advanced Maternal Age (Ma) Is Associated With An Increasedmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in a series of 137 miscarriages, Coulam et al (11) did not find a relation between ultrasound findings and karyotype. However, the sample included mainly women who had undergone fertility treatment or IVF, and the mean age of subjects was 36 years (11).…”
mentioning
confidence: 87%
“…But absence of embryonic pole development and fetal heart beat indicates that it prevents embryo development. Although, investigations of association between certain karyotype and ultrasonographic findings in failed pregnancies showed that correlation does not exist [Coulam et al, 1997], these four cases indicate that trisomy 1 correlates with diagnosis of blighted ovum. hCG, human chorionic gonadothropin; GS, gestational sac; YS, yolk sac; FHB, fetal heart beat; LMP, last menstrual period.…”
mentioning
confidence: 66%